PENERAPAN MODEL PBL BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA MATERI REFLEKSI DALAM TRANSFORMASI GEOMETRI DI SMP NEGERI 29 MEDAN - Agnes Venita Gultom; Amanda Nurhayati Siagian; Chintia Utami; Eka Novayanti Manalu; Hutabarat, Florentina; Maysaroh Pos Pos; Melisa Yessi Sagala; Rahel Valentina Br Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement of students’ mathematical representation abilities through the implementation of the STEM-based Problem Based Learning (PBL) model on reflection material at SMP Negeri 29 Medan. This study used a quantitative approach with a one group pretest-posttest design. The research subjects were ninth-grade students of SMP Negeri 29 Medan. The research instruments consisted of a mathematical representation ability test and student activity observation sheets. Data were collected through pretest, posttest, and observations. The data were analyzed using mean scores, N-Gain, and percentage of student activities. The results showed an improvement in students’ mathematical representation abilities after the implementation of the STEM-based PBL model. The average pretest score of 20.05 increased to 79.58 in the posttest, with an N-Gain score of 0.75 categorized as high. Student activities during the learning process were in the good to very good category. The use of the Autograph application helped students understand the concept of reflection more concretely and improved their visual and symbolic representation abilities. Based on the findings, the STEM-based PBL model was effective in improving students’ mathematical representation abilities on reflection material.